Surgeons performing self-surgery: A review from around the world - Chidinma Nwaogbe; Emily A. Simonds; Anthony V. D'Antoni; R. Shane Tubbs (Elsevier, 2018)
Surgery is an institution that has existed for thousands of years as a means of diagnosing, preventing or curing ailments. The commonplace assumption that a surgical procedure is performed by one party on another is not always true. There have been many documented cases of persons operating on themselves. Therefore, several cases of surgeons operating on themselves for various reasons are discussed in this article from a historical sense.